Nuclear mechanotransduction: Forcing the nucleus to respond - Guilluy, Christophe (Nucleus, 2015)
Cell phenotype and fate are driven by the mechanical properties of their surrounding environment. Changes in matrix rigidity or application of force have been shown to impact profoundly cell behavior and phenotype, demonstrating that the molecular mechanisms which “sense” and transduce these signals into biochemical pathways are central in cell biology. In this commentary, we discuss recent evidence showing that mechanotransduction mechanisms occur in the nucleus, allowing dynamic regulation of the nucleoskeleton in response to mechanical stress. We will review this nucleoskeletal response and its impact on both nuclear structure and function.